2004
DOI: 10.1074/jbc.m404449200
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed Mutagenesis Provides Insight into Racemization and Transamination of Alanine Catalyzed by Treponema denticola Cystalysin

Abstract: In addition to ␣, ␤-elimination of L-cysteine, Treponema denticola cystalysin catalyzes the racemization of both enantiomers of alanine accompanied by an overall transamination. Lys-238 and Tyr-123 or a water molecule located on the si and re face of the cofactor, respectively, have been proposed to act as the acid/base catalysts in the proton abstraction/donation at C␣/C4 of the external aldimine. In this investigation, two site-directed mutants, K238A and Y123F, have been characterized. The Lys 3 Ala mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…This proves that both MetC and MalY have cystathionine beta-lyase activity (52) and thus potentially similar catalytic mechanisms. Furthermore, it was recently reported that cystalysin from Treponema denticola possesses alanine racemase activity (4,7). E. coli MalY shows 51% sequence similarity to Treponema denticola cystalysin, and we found that a plasmid expressing E. coli MalY was indeed able to complement the alr/dadX deletion (data not shown).…”
Section: Discussionsupporting
confidence: 53%
“…This proves that both MetC and MalY have cystathionine beta-lyase activity (52) and thus potentially similar catalytic mechanisms. Furthermore, it was recently reported that cystalysin from Treponema denticola possesses alanine racemase activity (4,7). E. coli MalY shows 51% sequence similarity to Treponema denticola cystalysin, and we found that a plasmid expressing E. coli MalY was indeed able to complement the alr/dadX deletion (data not shown).…”
Section: Discussionsupporting
confidence: 53%
“…The system was stable after 90 ns of MD simulation. Moreover, to validate the behavior of the equilibrated system, interactions for PLP binding during PLP‐dependent lyase activity were verified to be well maintained along the MD simulations. In this regard, it is known that certain interactions are needed for proper functioning of the enzyme that are assumed to be maintained during MD simulations.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, to validate the behavior of the equilibrated system, interactions for PLP binding during PLP‐dependent lyase activity were verified to be well maintained along the MD simulations. In this regard, it is known that certain interactions are needed for proper functioning of the enzyme that are assumed to be maintained during MD simulations. These include: (a) a H‐bond between the phenolic hydroxyl group of Tyr55 and the phosphate group of PLP; (b) stacking between the aromatic side chain of Tyr114 with the pyridine ring of PLP; (c) a salt bridge between Arg351 and the carboxyl group of the ligand (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Additionally, it has been demonstrated that cystalysin has a high catalytic versatility and is able to catalyze the racemization and transamination of both enantiomers of alanine [319,320], the β-desulfination of L-cysteine sulfinic acid and the β-decarboxylation of L-aspartate and oxalacetate [321]. Recently, important hints were obtained on a possible prodrug that is activated by the parasite-specific enzyme and has anti-trichomonal activity in vivo.…”
Section: Methionine -Lyasementioning
confidence: 98%